Bark Effects on Stemflow Chemistry in a Japanese Temperate Forest I. The Role of Bark Surface Morphology - Oka, Ayano; Takahashi, Junko; Endoh, Yoshikazu; Seino, Tatsuyuki (Frontiers in Forests and Global Change, 2021)
Stemflow can be an important pathway for the drainage of precipitation and related solutes through tree canopies to forest soils. As stemflow must drain along bark surfaces, the effects of bark structure on stemflow chemical composition is merited. This study examines the relationship between stemflow chemistry and bark surface structure for six species of varying bark morphology (four deciduous broadleaf trees and two evergreen coniferous trees) at a montane and an urban site in Japan. Stemflow from smooth-barked species contained greater concentrations of solutes that appear to be rinsed from the stem surface (i.e., sea salt aerosols); while, rougher-barked tree species contained greater or less concentrations of solutes that appear to be leached (e.g., Ca2+) or taken-up (e.g., inorganic N) by the bark, respectively. Site-specific atmospheric environments also influenced thee bark-stemflow chemistry relationships—where the greater elemental deposition in the urban plot generally resulted in greater stemflow chemistry than observed in the lower-deposition montane plot. Our results therefore suggest that the dynamics of dry deposition wash-off by stemflow, and the exchange of dissolved solutes between stemflow and the bark surface, are influenced by the surface structure of the bark and the site’s atmospheric environment. Therefore, the interactions between bark surface structure and its surrounding atmospheric environment are important factors in the stemflow-related elemental cycling between the tree and precipitation.